Influence of low-level laser radiation on the physico-chemical indicators of biomembranes - Л. В. Січевська; Т. M. Овсяннікова; А. О. Коваленко; І. А. Забєліна; О. М. Левченко; О. В. Гурін; В. П. Берест (Біофізичний вісник)
Background: The study of physical and molecular mechanisms of the influence of low-level laser radiation (LLLR) of a wide frequency range on biological objects allows to clarify the problem of laser photomodulation at the level of natural biological membranes and their model analogues.